2020
DOI: 10.3122/jabfm.2019.01.190238
|View full text |Cite
|
Sign up to set email alerts
|

A New Quality Improvement Toolkit to Improve Opioid Prescribing in Primary Care

Abstract: The role of opioids in managing chronic pain has evolved in light of the opioid misuse epidemic and new evidence regarding risks and benefits of long-term opioid therapy. With mounting national guidelines and local regulations, providers need interventions to standardize and improve safe, responsible prescribing. This article summarizes the evolution of an opioid management toolkit using a quality improvement (QI) approach to improve prescribing. Methods: The authors developed a list of opioid-prescribing best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this study, we set out to investigate sources, secondary uses, and key considerations for optimising primary care prescribing data and its actionability for quality of care related decision-making. Much of the existing literature on measurement for improving primary care prescribing focuses on implementation sciences and practice-level interventions (eg, [44][45][46] ). There is also a dedicated field of research on improving prescribing through interventions in direct patient care (eg, [27][28][29] ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we set out to investigate sources, secondary uses, and key considerations for optimising primary care prescribing data and its actionability for quality of care related decision-making. Much of the existing literature on measurement for improving primary care prescribing focuses on implementation sciences and practice-level interventions (eg, [44][45][46] ). There is also a dedicated field of research on improving prescribing through interventions in direct patient care (eg, [27][28][29] ).…”
Section: Discussionmentioning
confidence: 99%
“…Portions of the Toolkit were iteratively developed in previous studies. 16,[21][22][23] In keeping with the pragmatic design of this study, each team tailored its use of the Toolkit according to the needs of the practice, including determining when to start within a 2-year timeframe and which components of the intervention to use.…”
Section: Ibh and Primary Care (Ibh-pc) Interventionmentioning
confidence: 99%
“…Sokol's team 4 used 2 models of change to promote practice improvement for care to both those with OUD and those who are prescribed opioids. Articles by van Eeghen et al 5 ing by state. Jerant et al 8 looked at patient satisfaction related to opioids and found that 6 or more opioid prescriptions per year was associated with higher patient satisfaction.…”
Section: Family Medicine Carementioning
confidence: 99%